IMPROVISASI GURU PENGGERAK DALAM IKEBIJAKAN MERDEKA BELAJAR - Lama'a Zahra, Bahezta (TAZKIA JURNAL, 2024)
The purpose of this study is to understand how to execute kemandirian learning with the guidance of a peer tutor. This study employs the kualitatif method of research methodology. The type of research that this pertains to is called library research. In this research, content analysis, or isi analysis, is the technique used for data analysis. The systematic study methodology is based on the research question and goal. This study's methodology outlines the strategies used by educators to motivate their students, including: (1) serving as a motivator in the classroom based on students' efforts to learn; (2) encouraging teachers to help students develop their leadership skills by guiding and preparing them for their future careers in a holistic manner; and (3) changes in the way that teachers motivate their students, which stem from sentralistic teachers' push toward institutional desentralization.